Path conditions monitoring for a power wheel chair - Pham, Quoc Trung. (2009)
Nowadays detecting outer conditions is emerging as one of the most important issues in Robotics area. We need to detect and process all outer conditions quickly and sensors cannot satisfy these requirements due to a lot of complex calculations. Therefore we need to develop a new method to simplify these sensing processes. This report describes the experiment process for monitoring path conditions of a Power Wheel Chair inside and outside Mechatronics Lab, School of Mechanical and Aerospace, NTU using impedance transduction method. This method is based on the relationship between electrical and mechanical impedance at the DC motor of the wheel chair. The Power Wheel Chair has two DC-motors attached to two rear wheels and a joystick at front is used to adjust the direction as well as the speed of the wheel chair. The wheel chair will counter different speed levels and loading conditions inside and outside the lab such as turning and obstacles. A Voltage Probe and Current Probe will be used to detect the changing Voltage and Current supplied to two DC motors when the wheel chair is moving and the signal will be recorded by Digital Signal Analyzer (DSA) at the same time. Finally, all data recorded will be processed by using MATLAB, different graphs for various conditions will be plotted to make the conclusion about the relationship between these conditions and the changing of Voltage, Current. At the end of this project, the author can obtain a list of relationships between electrical impedance and specific path conditions, therefore the path conditions can be decided quickly by observing the electrical impedance collected.